A case of Vipera ammodytes bite in a companion dog - Nikolić Sonja (Veterinarski Glasnik)
On April 1, 2024, outside a family house in a village in the foothills of Rudnik Mountain, a female shar pei companion dog was bitten by a nose-horned viper, Vipera ammodytes. The dog was taken to a veterinarian and received symptomatic therapy but not antivenom. The first night the dog’s state was very bad. For the following two days, she was lethargic and refused food and water. The oedema, which developed on her snout and spread to the abdomen, persisted for 3-4 days. After six days, the dog had fully recovered. In Serbian veterinary journals, reports describing the effects of snake bites on dogs are lacking; even in foreign scientific literature, there are few data regarding V. ammodytes bites in companion animals. Therefore, the present report could be useful for veterinarians and dog owners.